Preparation of three‐notochord explants for imaging analysis of the cell movements of convergent extension during early Xenopus morphogenesis. (13th September 2021) - Goto, Toshiyasu; Keller, Ray
Abstract: We describe a method of generating three‐notochord explants to analyze the cell movements of convergent extension (CE) during Xenopus laevis gastrulation and neurulation. This method uses standard microsurgical techniques under a fluorescence stereomicroscope to combine notochordal sectors of gastrulae, side by side (lateral surfaces apposed) into a single explant. Three‐notochord explants cultured on bovine serum albumin (BSA)‐coated glass converged mediolaterally and extended in the anterior–posterior direction. The individual notochordal cells showed the mediolaterally oriented, bipolar tractional motility and the resulting mediolaterally oriented cell intercalation characteristic of CE, thereby reproducing both the in vivo tissue and the cell movements in an explant. Image analysis of three‐notochord explants reveals the effects of overexpressions or knockdowns of genes, of manipulation of the extracellular matrix, and of exposure to chemical reagents on morphogenesis during gastrulation and neurulation, compared with control explants. Moreover, since three‐notochord explants provide two zones of cell intercalation between notochords, individual cell behaviors between notochords of different characteristics and experimental treatments can be observed at the same time. Abstract : Imaging analysis of three‐notochord explants.